2009
DOI: 10.4076/1757-1626-2-6746
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous azygos venous system in a south Indian cadaver: a case report

Abstract: IntroductionThe posterior thoracic wall, an area drained by the azygos venous system, is a common site for surgical intervention. Since the venous part of the cardiovascular system is subject to most common variation, abnormalities in the azygos venous system are often reported.Case presentationDuring routine dissection classes for undergraduate medical students, we encountered a variation in the azygos venous system in a 65 years old south Indian male cadaver. We observed that there was no accessory azygos ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
1
2
1
1
Order By: Relevance
“…The left azygos venous line makes the superior and inferior Hemi-azygos veins. In the present study, we found that the accessory hemiazygos veins were the most variable veins, in contrast to the previous studies which reported azygos veins as the most variable veins [9,10] and these accessory hemizygous veins might pour into the left brachiocephalic, hemiazygos, or azygos vein. Mostly, the conspicuous 'right-sided azygos vein with few representatives of the hemiazygos veins are present.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The left azygos venous line makes the superior and inferior Hemi-azygos veins. In the present study, we found that the accessory hemiazygos veins were the most variable veins, in contrast to the previous studies which reported azygos veins as the most variable veins [9,10] and these accessory hemizygous veins might pour into the left brachiocephalic, hemiazygos, or azygos vein. Mostly, the conspicuous 'right-sided azygos vein with few representatives of the hemiazygos veins are present.…”
Section: Discussioncontrasting
confidence: 99%
“…Three connected major veins exist in the azygos system, namely, the hemiazygos vein, accessory hemiazygos vein, and azygos vein in the context of CT and MRI of the mediastinum is crucial, as a few of the anomalies of this system could be misinterpreted with various other pathological conditions such as aneurysms, enlarged lymph nodes, and tumors [9]. For a long, researchers have been extensively involved in deciphering the different types of classification of the azygos system [2,10], but still, this topic is a matter of debate and further investigation. Keeping this in view, this study aimed to observe the population-specific changes in the azygos system among the Eastern Indian population.…”
mentioning
confidence: 99%
“…13 Another description is for an incomplete accessory HV with the posterior intercostal veins draining directly to the AV. 14 A large number of studies show the absence of one or more components of the ASV, 5,[14][15][16] although no study has found any variation similar to the one presented in the present article. The HAV is the most variable component of the ASV in terms of absence, number of branches, communications, and level of termination.…”
Section: Discussionsupporting
confidence: 48%
“…Absence of superior and inferior venae cavae and azygos continuation of inferior vena has been reported. 8 Absence of accessory hemiazygos vein and termination of left 4-7 th posterior intercostal veins into azygos vein has been reported by Quadros et al 9 A case of communication between pulmonary veins and azygos vein has been reported by Lapierre et al 10 Very rarely the azygos vein may terminate in the left superior vena cava. One such variation has been reported by Uemura et al 11 The connection between azygos vein and portal venous system provides the blood flow to the superior vena cava through the esophageal veins in case of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%